2013
DOI: 10.1002/jbm.b.32859
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the mold temperature on the mechanical properties and crystallinity of hydroxyapatite whisker‐reinforced polyetheretherketone scaffolds

Abstract: Porous and bioactive polyetheretherketone (PEEK) scaffolds have potential to replace metallic scaffolds for biologic fixation of permanent implants adjacent to trabecular bone, such as interbody spinal fusion devices. The objective of this study was to investigate the effects of the mold temperature and PEEK powder on the mechanical properties and crystallinity of hydroxyapatite (HA) whisker-reinforced PEEK scaffolds prepared using compression molding and porogen leaching. Scaffolds were prepared at mold tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Based on the reported positive effects of using high temperatures on both shear viscosity of PEEK and mechanical properties of the resulting compression molded parts [53,54] with no adverse effect on biocompatibility in vivo [54], a mold temperature of 400 °C was selected in this study. While mold temperatures of 400 °C guarantee minimum viscosity, caution must be exercised when working at temperature in excess of 380 °C as there is a risk of thermal oxidation [55]. Potential for oxidation can be decreased by a reduction in dwell time spent at the target temperature; such optimization of dwell time is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the reported positive effects of using high temperatures on both shear viscosity of PEEK and mechanical properties of the resulting compression molded parts [53,54] with no adverse effect on biocompatibility in vivo [54], a mold temperature of 400 °C was selected in this study. While mold temperatures of 400 °C guarantee minimum viscosity, caution must be exercised when working at temperature in excess of 380 °C as there is a risk of thermal oxidation [55]. Potential for oxidation can be decreased by a reduction in dwell time spent at the target temperature; such optimization of dwell time is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…During layer-by-layer manufacturing, residual stress is accumulated, leading to warping and interlayer delamination [78,79]. These problems are more important for additive manufacturing of semi-crystalline polymers with a high melting temperature such as PEEK and can significantly affect dimensional accuracy and mechanical properties [80][81][82]. In fact, the degree of crystalline perfection of PEEK is considerably influenced by the rate of cooling and thermal gradient during crystallisation from melt [83].…”
Section: Challenges Of 3d Printing Of Peekmentioning
confidence: 99%
“…Conrad et al [26] demonstrated that this increased mould temperature may also increase the compressive modulus, yield strength and strain of the traditional PEEK/HA composites. Working temperatures greater than 380℃ have been shown to reduce crystallinity, which is known to be beneficial for ductility and toughness [27,28] , with no adverse effect on biocompatibility in vivo [27] . Given the positive effects described on both shear viscosity and mechanical properties of the resulting PEEK samples, a mould temperature of 400℃ was selected for this study.…”
Section: Resultsmentioning
confidence: 99%